IMPLEMENTASI E-COMMERCE DAN E-BUSINESS DALAM MENINGKATKAN DAYA SAING UMKM DI ERA DIGITAL - Ratnawita, Ratnawita; Veri, Jhon (Jurnal Ekonomi Bisnis Kompetif, 2025)
The digital transformation has encouraged Micro, Small, and Medium Enterprises (MSMEs) to adopt technology in order to maintain and enhance competitiveness in an increasingly competitive market. This study aims to examine the implementation of e-commerce and e-business in improving the competitiveness of MSMEs in the digital era. The method used is a qualitative descriptive approach with data collection techniques through in-depth interviews, observations, and document studies on several MSMEs that have applied digital technology in their business operations. The results show that the utilization of e-commerce can expand market reach, increase transaction efficiency, and accelerate marketing processes. Meanwhile, the implementation of e-business supports more effective internal operational management, such as inventory management, customer service, and information systems. The combination of both has been proven to increase productivity and strengthen the position of MSMEs in digital market competition. The implication of these findings indicates that support for digital literacy and technological infrastructure is crucial to encourage comprehensive and sustainable digital transformation of MSMEs.. Keywords: Digital Era, Digital Transformation, E-Business, E-Commerce, MSME Competitiveness